Chongqing 2035 : Spatial and Economic Transformation for a Global City - World Bank (World Bank, Washington, DC, 2019)
Geographically, Chongqing is strategically positioned as a gateway to China’s west, a key connection in the Yangtze river economic belt, and a strategic base for China’s belt and road initiative. Over the past two decades, Chongqing has faced significant challenges, including the resettlement of over 1 million people and numerous enterprises due to the construction of the Three Gorges dam. Despite these challenges, Chongqing has made an extraordinary transformation. This transformation has resulted in an important sectoral shift. The municipality’s economy, formerly based in agriculture and heavy industry, is now more balanced, with the secondary and tertiary industries contributing to 44 percent and 48 percent of gross domestic product (GDP) respectively. Chongqing’s economic transformation goes hand in hand with improvements to social inclusiveness.